Conceptualizing information technology governance model for higher education: An absorptive capacity approach - Ajayi, Binyamin Adeniyi; Hussin, Husnayati (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI), Universitas Ahmad Dahlan, 2018)
Information Technology (IT) governance has been emerging as a central issue in many organizations. This is because IT governance is key to realizing IT business value. Past studies have focused on the three aspects of IT governance, namely, structural capability, process capability and relational capability. At the same time, some studies have suggested that IT governance process should be viewed as a learning process rather than a problem solving process. Based on this scenario, the role of knowledge and knowledge based processes should be the central focus of IT governance. As a learning process, IT governance effectiveness can be determined by how much impact IT governance practices has influenced on decision-makers’ thinking and actions. In this case, knowledge capacity absorbed from IT governance experience reflects a certain level of organizational learning (OL) achieved which later influences the level of IT governance performance. Since studies that adopt this perspective is lacking, this paper proposes a conceptual framework based on absorptive capacity approach for an IT governance performance model in the higher education. The paper contributes theoretically by extending the knowledge of IT governance by exploring a new perspective on OL.